Application and Typical Case of Unmanned Aerial Vehicles Combined with Building 3D Modeling. Issue 1 (January 2021) - Li, Minhui; Yin, Hang; Cheng, Dongji; Xu, Xinli; He, Ya
Abstract: With the development of unmanned aerial vehicle (UAV) technology, the application of UAV is becoming more and more extensive, including the application of UAV in building 3D modeling. This paper introduces the composition of commonly used related equipment and some key UAV technologies combined with building 3D modeling: 3D laser scanning technology, Photogrammetry, Multi-view 3D reconstruction technology and Seismic disaster prevention technology. This paper also studies practical applications and related cases. On the one hand, UAV can be used in the protection of ancient building heritage. Combined with photography, measurement, modeling technology, UAVs can rapid and efficient access to relevant building three-dimensional information, including building damage and overall configuration, then provide important information and reference for building heritage protection. On the other hand, UAVs can also carry out multi-faceted evaluation and survey of modern buildings, collect topography, guide seismic planning and post-disaster reconstruction, and save project costs.